The Age of Adversity : The Fourteenth Century - Lerner, Robert E. (The Development of Western Civilization, 2019)
The fourteenth century has usually been dismissed as a period of irrelevant misfortune and confusion. In this latest addition to the popular Development of Western Civilization series, however, Professor Lerner demonstrates that the age, in its response to natural disasters and to the collapse of the overextended ambitions of the previous century, initiated some of the most fundamental of modern beliefs and social structures. The author's fluent summary of this period of catastrophe and triumph provides a concise and readable story of the decline of the medieval world and premonitions of the Renaissance.